The quantum structure of space and time : proceedings of the 23rd Solvay Conference on Physics, Brussels, Belgium, 1-3 December, 2005 - Gross, D. (David Jonathan); Henneaux, Marc; Sevrin, A. (Alexander) (World Scientific, 2007)
Ever since 1911, the Solvay Conferences have shaped modern physics. The 23rd edition, chaired by 2004 Nobel Laureate David Gross, did not break with that tradition. It gathered most of the leading figures working on the central problem of reconciling Einstein's theory of gravity with quantum mechanics. These proceedings give a broad overview with unique insight into the most fundamental issues raised by this challenge for 21st century physics, by distinguished renowned scientists. The contributions cover: the status of quantum mechanics, spacetime singularities and breakdown of classical space.